The role of reconstructive plastic surgery in the treatment of victims of the 2023 Kahramanmaraş earthquake - Aksöyler, Dicle; Akpınar, Ömer Faruk; Kozanoğlu, Erol; Akalın, Bora Edim; Bingül, Emre Sertaç; Mirasoğlu, Bengüsu; Berköz, Ömer; Arıncı, Rifat Atilla (Acta Medica, 2024)
Objective: As a result of the 2023 Kahramanmaraş earthquake, medical institutions experienced a large influx of patients requiring acute multidisciplinary surgical and medical care. This study aimed to evaluate the patient demographics and treatment management of survivors admitted to our reconstructive plastic surgery department. Materials and Methods: We retrospectively analyzed the age, sex, time under the wreckage, time of admission, types and locations of injuries, treatment modalities, receipt of hyperbaric oxygen therapy, and receipt of vacuum-assisted closure therapy of the earthquake victims referred to our department. Results: The definitive management of all 42 earthquake survivors admitted to our department was reviewed. This included five free flaps, four regional flaps, 18 split-thickness skin grafts, and one maxillofacial fracture repair. Eight patients were treated conservatively including two with non-displaced maxillofacial fractures. Of the 26 patients treated for lower extremity injuries, four were already amputees. Among the remaining 22 patients with such injuries, one underwent Charcot amputation plus free flap reconstruction to preserve extremity length and one underwent below-the-knee amputation. Of the 16 upper extremity injuries, two patients referred with extensive forearm necrosis underwent forearm amputation. To preserve extremity length and ensure the limbs were suitable for biomechanical orthoses, free transverse upper gracilis musculocutaneous flaps and free chimeric Anterolateral- Vastus Lateralis musculocutaneous flaps were performed. Conclusion: This study illustrates the value of multi-modal reconstructive plastic surgery in the treatment of disaster survivors, particularly in the management of multi-trauma.